2021
DOI: 10.1029/2021jd034653
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the CAM6 Climate Model Using Cloud Observations at McMurdo Station, Antarctica

Abstract: Simulating clouds is an intricate challenge for global climate models (GCMs). In pursuit of improving the fidelity of future climate prediction, a better understanding of cloud radiative effects and the environmental conditions for cloud formation is needed. To estimate cloud radiative effects, models must accurately represent physical processes occurring during cloud formation and evolution, in order to capture cloud microphysical properties (e.g., mass and number concentrations of cloud hydrometeors) and mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 88 publications
2
9
0
Order By: Relevance
“…The E3SM in-cloud frequency shows a sudden increase below −20°C in the 60°-70°S latitudinal bin which is not seen in the observations. This is consistent with a recent study which showed that the Community Atmosphere Model version 6 (CAM6) climate model (i.e., a model with similar cloud microphysics parameterizations to E3SM version 1) tends to overestimate cloud fraction and cloud height at higher latitudes (Yip et al, 2021).…”
Section: Statistical Distributions Of Cloud Phase With Respect To Tem...supporting
confidence: 92%
See 2 more Smart Citations
“…The E3SM in-cloud frequency shows a sudden increase below −20°C in the 60°-70°S latitudinal bin which is not seen in the observations. This is consistent with a recent study which showed that the Community Atmosphere Model version 6 (CAM6) climate model (i.e., a model with similar cloud microphysics parameterizations to E3SM version 1) tends to overestimate cloud fraction and cloud height at higher latitudes (Yip et al, 2021).…”
Section: Statistical Distributions Of Cloud Phase With Respect To Tem...supporting
confidence: 92%
“…Tuning the model parameterization to allow more SLW has been found to reduce the shortwave bias (Kay, Bourdages, et al., 2016; Kay, Wall, et al., 2016). Observations have confirmed that cloud top SLW layers are common over the SO and Antarctica (Yip et al., 2021; D. Zhang et al., 2010; D. Zhang et al., 2019; Y. Zhang et al., 2019). Analysis of satellite data further shows that cloud top phase varies with latitudes (Mace, Protat, & Benson, 2021).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The newer CAM6 has enhancements to cloud ice nucleation and simulates increased supercooled liquid (Gettelman et al, 2020). Yip et al (2021) found that in contrast to the CAM5 results, CAM6 frequently overstimulates liquid water at McMurdo. While this may appear to be a contrarian result, it may emphasize the need for improved modeling of cases with enhanced ice particle amounts.…”
Section: Discussionmentioning
confidence: 93%
“…Yip et al. (2021) found that in contrast to the CAM5 results, CAM6 frequently overstimulates liquid water at McMurdo. While this may appear to be a contrarian result, it may emphasize the need for improved modeling of cases with enhanced ice particle amounts.…”
Section: Discussionmentioning
confidence: 94%